Drivers of user engagement in eWoM communication. Issue 5 (8th August 2016) - Rossmann, Alexander; Ranjan, Kumar Rakesh; Sugathan, Praveen
Abstract : Purpose: This paper aims to complement the current understanding about user engagement in electronic word-of-mouth (eWoM) communications across online services and product communities. It examines the effect of the senders' prior experience with products and services, and their extent of acquaintance with other community members, on user engagement with the eWoM. Design/methodology/approach: The study used a sample of 576 unique user postings from the corporate fan page of two German firms: a service community of a telecom provider and a product community of a car manufacturer. Multiple regression analysis is used to test the conceptual model. Findings: Senders' prior experience and acquaintance positively affect user engagement with eWoM, and these effects differ across communities for products and services and across their influence on "likes" and "comments". The results also suggest that communities for products are orientated toward information sharing, while those discussing services engage in information building. Research limitations/implications: This research explains mechanisms of user engagement with eWoM and opens directions for future research around motives, content and social media tools within the structures of online communities. The insights on information-handling dimensions of online tools and antecedents to their use contribute to the research on two prioritized topics by the Marketing Science Institute – "Measuring and Communicating the Value of Online Marketing Activities and Investments" and "Leveraging Digital/Social/Mobile Technology". Practical implications: This research offers insights for firms to leverage user engagement and facilitate eWoM generation through members who have a higher number of acquaintances or who have more experience with the product or service. Executives should concentrate their community engagement strategies on the identification and utilization of power users. The conceptualization and empirical test about the role of likes and comments will help social media managers to create and better capture value from their social media metrics. Originality/value: The insights about the underlying factors that influence engagement with eWoM advance our understanding about the usage of online content.